2003
DOI: 10.1177/172460080301800202
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Breast Carcinoma: Prognostic Implications of P53 Expression

Abstract: Medullary breast carcinoma (MBC) is a rare pathological type of breast cancer. The rate of p53 protein accumulation is higher in MBC than in common invasive ductal carcinoma. Whether this particular feature of MBC influences the outcome after treatment is unknown. We retrospectively analyzed the characteristics, treatment and outcome of 71 patients with MBC treated between 1981 and 1996. The median age was 51 years (range 27-81) and the median clinical tumor size was 25 mm (range 0-70 mm). Breast-conserving tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
(37 reference statements)
1
7
0
1
Order By: Relevance
“…Our study demonstrates that MBCs effectively presented a high number of gains and losses, suggesting a putative alteration within a DNA damage repair process. If confirmed, this hypothesis could lead to an explanation of their higher sensitivity to radiation therapy and their favorable local and regional outcome [11,12]. These features have already been reported for BRCA1/2 -related tumors [37,38].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our study demonstrates that MBCs effectively presented a high number of gains and losses, suggesting a putative alteration within a DNA damage repair process. If confirmed, this hypothesis could lead to an explanation of their higher sensitivity to radiation therapy and their favorable local and regional outcome [11,12]. These features have already been reported for BRCA1/2 -related tumors [37,38].…”
Section: Discussionmentioning
confidence: 67%
“…MBCs have recently been shown to share the basal-like immunophenotype [9], and some morphological traits that have been reported to be specific for BLC with poor prognosis, such as tumor necrosis, a pushing border of invasion, and a stromal lymphocytic infiltrate [22,25], are also observed in MBCs. These phenotypic and immunophenotypic similarities suggest that these two entities have a common biology despite the fact that MBC presents a more favorable outcome [11,12]. In the present study we wished to define the possible phenotypic and genetic differences between MBCs and BLCs with a view to understanding the major differences in clinical outcome between these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that lymphoid infiltration is of poor prognosis in Grade‐3 BC patients younger than 35,10 and in invasive micropapillary carcinomas 11. In contrast, MBC is characterised by both improved clinical outcome and prominent lymphocyte infiltrate 12, 13. In a recent study of a large BC series, prominent inflammation was associated with better prognosis 14.…”
mentioning
confidence: 99%
“…In a series of medullary carcinomas (n = 41), high radiosensitivy was suggested (7% of the patients had a complete response after a dose of 55–60 Gy) and chemotherapy had no effect on the rate of recurrence or survival (6-year local recurrence-free survival, metastasis-free survival, and survival rates were 86%, 83%, and 83%, respectively) 65. Another series of medullary carcinomas (n = 71), also presented with good outcomes (10-year distant metastasis-free survival of 81.4%) with chemotherapy only given to a minority (n = 11) 66. Good outcomes (14-year distant recurrence-free interval of 89% for ER-negative medullary breast cancer) were also noticed in the International Breast Cancer Study Group (IBCSG) (n = 127), but almost 70% received adjuvant chemotherapy 67.…”
Section: Clinical and Pathological Presentationmentioning
confidence: 97%